Peran Kompensasi, Disiplin Kerja, dan Motivasi dalam Meningkatkan Kinerja Karyawan - Anang Tri Wahyono; Diovani Tirtana; Suprihati Suprihati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Employee performance, which is a reflection of their competence in completing tasks, is very important for achieving organizational goals. Therefore, improving performance is a top priority for the company.This quantitative research aims to analyze the factors that influence employee performance in the Quality Control division of PT. Hwa Seung Indonesia, Jepara. Of the total 174 employees, 121 were used as research samples selected using the Slovin formula. Data collection was carried out through questionnaires with saturated sampling techniques. The collected data was then analyzed using various statistical methods, including multiple linear regression analysis. The research results show that the variables workload, compensation (t-value 2.865), work discipline (t-value 4.707), and motivation (t-value 4.425) together have a positive and significant influence on employee performance.